The thrombotic microangiopathy Registry of North America: A United States multi‐institutional TMA network. Issue 5 (17th November 2015) - Metjian, Ara; Tanhehco, Yvette C.; Aqui, Nicole; Bhoj, Vijay G.; Jamensky, Lita; Marques, Marisa B.; Onwuemene, Oluwatoyosi; Pham, Huy P.; Arepally, Gowthami M.
Abstract : The thrombotic microangiopathy (TMA) Registry Network of North America (TRNA) is a collaborative network organized for the purpose of developing a multi‐institutional registry and network to conduct clinical studies in a rare patient population. The TRNA was founded in 2013 by four academic medical centers (Columbia University Medical Center, Duke University Medical Center, University of Alabama at Birmingham, and University of Pennsylvania) to develop a national and demographically diverse dataset of patients with TMA. A clinical database was developed by network members using REDCap (Research Electronic Data Capture), a web‐based database developed for clinical research. To facilitate rapid Institutional Review Board (IRB) approval at multiple sites, the TRNA utilized IRBshare, a streamlined IRB process to allow patient recruitment and enrollment into the TMA registry. This article reviews the process used to establish the TRNA network and discusses the significance of the first multi‐institutional clinical apheresis network developed in the United States. J. Clin. Apheresis 31:448–453, 2016. © 2015 Wiley Periodicals, Inc.